2016
DOI: 10.1016/j.molbiopara.2016.09.001
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of the recombination activities of the Entamoeba histolytica Rad51 recombinase

Abstract: The protozoan parasite responsible for human amoebiasis is Entamoeba histolytica. An important facet of the life cycle of E. histolytica involves the conversion of the mature trophozoite to a cyst. This transition is thought to involve homologous recombination (HR), which is dependent upon the Rad51 recombinase. Here, a biochemical characterization of highly purified ehRad51 protein is presented. The ehRad51 protein preferentially binds ssDNA, forms a presynaptic filament and possesses ATP hydrolysis activity … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
15
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 9 publications
(15 citation statements)
references
References 78 publications
(160 reference statements)
0
15
0
Order By: Relevance
“…DIDS is a commercially-available small molecule inhibitor of human Rad51 [19], a DNA recombinase that regulates homology search and strand exchange during homologous recombination. We have previously shown that DIDS decreases the activity of eh Rad51, the Entamoeba ortholog of Rad51, and inhibits encystation [20]. E. invadens cells were induced to encyst in the absence or presence of DIDS (30 µM or 150 µM) for 48 h. Manual counting of detergent-resistant cells confirmed that DIDS inhibits terminal differentiation (Fig.…”
mentioning
confidence: 56%
See 1 more Smart Citation
“…DIDS is a commercially-available small molecule inhibitor of human Rad51 [19], a DNA recombinase that regulates homology search and strand exchange during homologous recombination. We have previously shown that DIDS decreases the activity of eh Rad51, the Entamoeba ortholog of Rad51, and inhibits encystation [20]. E. invadens cells were induced to encyst in the absence or presence of DIDS (30 µM or 150 µM) for 48 h. Manual counting of detergent-resistant cells confirmed that DIDS inhibits terminal differentiation (Fig.…”
mentioning
confidence: 56%
“…Trophozoites (Control) were induced to encyst for 48 h in the presence of Gal (10 mM [6]), GlcNAc (10 mM [6]), GalNAc (10 mM [6]) or DIDS (30 µM or 150 µM [20]). Cells or DRCs were stained and analyzed as described in Fig.…”
Section: Figmentioning
confidence: 99%
“…The data described, include supporting information on sequence conservation and identity of Rad51 for the analysis by Kelso et al, in press [1]. A Rad51 amino acid sequence alignment from nineteen different vertebrate and invertebrate organisms is shown.…”
Section: Datamentioning
confidence: 86%
“…3). A comparison of Entamoeba histolytica Rad51 to the other species was analyzed in the previously mentioned article [1] and by Lopez-Casamichana et al, 2008 [4].…”
Section: Datamentioning
confidence: 99%
“…Biochemically, Lopez-Casamichana et al (2008) showed that partially purified Eh Rad51 bound DNA and facilitated homologous DNA pairing ( Lopez-Casamichana et al, 2008 ). The findings were recently extended by a report that demonstrated Eh Rad51 was not only capable of binding DNA and forming D-loops, but that Eh Rad51 hydrolyzed ATP, formed presynaptic filaments, and catalyzed DNA strand exchange over thousands of base pairs ( Kelso et al, 2016 ). Although E. histolytica reproduce asexually through binary fission, the occurrence of meiosis in E. histolytica was first proposed to occur during encystation based on increased expression of meiosis-specific genes ( Ehrenkaufer et al, 2013 ).…”
Section: Homologous Recombination In Protozoan Parasitesmentioning
confidence: 83%